Framing the Schemata: Western Media Coverage of African Technological Innovations - Gregory Gondwe (Journalism and Media)
This study examines the framing of African technological innovations in Western media over the past two decades (2003–2023), focusing on four case studies: M-Pesa, LifeBank, FarmDrive, and NigeriaSat-1. Using a qualitative research design that integrates content analysis and framing theory, we analyze how major media outlets, including the BBC, CNN, The Guardian, Reuters, and The New York Times, represent African innovations. The analysis reveals that media coverage tends to frame these innovations primarily through a humanitarian lens, emphasizing their role in addressing poverty, healthcare, and food security challenges. While highlighting the social impact of these technologies, this narrative often overlooks their broader potential for global scalability and industry disruption. To complement the content analysis, we conducted 24 semi-structured interviews with tech entrepreneurs, media professionals, and scholars from Kenya, Ghana, Nigeria, and Senegal, investigating their perspectives on how Western media coverage impacts investment and collaboration in African technological sectors. The interview findings confirm that such media portrayals hinder international investment and partnership opportunities by reinforcing the narrative that African technologies are primarily crisis management tools, rather than innovative solutions with global market potential. This article argues for a shift in this narrative, recommending policies that include strategic media advocacy, enhanced public relations, and increased investment in Research and Development.